2002
DOI: 10.1002/1521-3900(200206)182:1<273::aid-masy273>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide mediated living radical polymerization in miniemulsion

Abstract: The introduction of the aqueous phase into a living radical polymerization increases the complexity of the kinetics by creating the possibility of species partitioning between the aqueous and organic phases, and introducing aqueous phase reactions which could play a significant role particularly in chain initiation and/or particle nucleation. We have conducted a series of styrene miniemulsion polymerizations in which the solubility of initiator and nitroxide have been systematically varied. Experiments were ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…Pan et al [4] used TEMPO-terminated oligomers of polystyrene as a macroinitiator to initiate the miniemulsion polymerization of styrene at 125uC and found that the molecular weight distribution of the PS products was not narrow. Cunningham [5] compared miniemulsion polymerization of styrene in TEMPO/ benzoyl peroxide (BPO), TEMPO/potassium persulfate (KPS), 4-hydroxy-2,2,6,6-tetramethyl-piperidinyloxy (HTEMPO)/BPO and HTEMPO/KPS four different systems. They also studied the influence of the rateaccelerating additive camphorsulfonic acid (CSA) in heterogeneous styrene miniemulsion polymerizations with TEMPO/BPO and HTEMPO/BPO systems, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al [4] used TEMPO-terminated oligomers of polystyrene as a macroinitiator to initiate the miniemulsion polymerization of styrene at 125uC and found that the molecular weight distribution of the PS products was not narrow. Cunningham [5] compared miniemulsion polymerization of styrene in TEMPO/ benzoyl peroxide (BPO), TEMPO/potassium persulfate (KPS), 4-hydroxy-2,2,6,6-tetramethyl-piperidinyloxy (HTEMPO)/BPO and HTEMPO/KPS four different systems. They also studied the influence of the rateaccelerating additive camphorsulfonic acid (CSA) in heterogeneous styrene miniemulsion polymerizations with TEMPO/BPO and HTEMPO/BPO systems, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] As far as we are aware, there are to date no systematic studies on particle size effects in NMP in miniemulsion, although scattered information exists with regards to differences between miniemulsion and bulk for TEMPO-mediated radical polymerization of S in miniemulsion. In most cases, S/TEMPO miniemulsion polymerizations using macroinitiator (polystyrene (PS)-TEMPO), [21,22] benzoyl peroxide/ TEMPO [23,24] or potassium persulfate/TEMPO [24][25][26][27] give R p values very similar to those in bulk. [28] Cunningham and coworkers [29,30] reported a strong dependence of R p in S/PS-TEMPO miniemulsion on the amount of the surfactant sodium dodecylbenzenesulfonate (SDBS) (the particle size distributions were ''nearly identical'' with a ''mean diameter'' of 150 nm), and speculated that SDBS or SDBS impurities consume nitroxide, thus resulting in an increase in R p .…”
Section: Introductionmentioning
confidence: 99%
“…From a practical point of view, although it has been experimentally found that a ratio of TEMPO to the initiator of about 1.3 generally works well in bimolecular bulk NMP,12 the presence and length of an induction period will be rather sensitive to the ratio used, as any shortage of the initiator will generate and increase this period. Also, bimolecular systems may present additional complex behavior, especially in heterogeneous reactions,35 which may be difficult to interpret. Clearly, a better understanding of the induction period is needed.…”
Section: Introductionmentioning
confidence: 99%